'Destroying barriers to critical thinking' to surge the effect of self-leadership skills on electronic learning styles. (December 2022) - Durnali, Mehmet
Highlights: Self-leadership negatively predicted critical thinking barriers. Critical thinking barriers negatively predicted electronic learning styles. Self-leadership positively predicted electronic learning styles. For advancing teacher candidates' skills in getting rid of barriers to critical thinking, attention should be given to promote them to find their accurate learning styles through practicing self-leadership. The results provided evidence for understanding the theories of critical thinking barriers, self-leadership and electronic learning styles. Abstract: A good deal of data-driven results of current research supported the importance of fostering critical thinking skills of teachers and students. Particularly, there has been a debate about how to handle the barriers to critical thinking. To cope with critical thinking barriers, I comfortably argue that self-leadership skills of teacher candidates can be empowered at the first stage and then their electronic learning styles can be cultivated and improved. Missing from the literature is a structural equation model testing the empirical rationality of three salient subjects and yet their interrelated links. To that end, this research aimed to examine the relationships between self-leadership skills, critical thinking barriers, and electronic learning styles among teacher candidates in an electronic-based education setting adjusted after the outbreak of COVID-19. This correlational study tested a literature-based hypothetic model. The data were gathered from 476 teacher candidates. 365 of these were females and 111 were males. Participants selected from those who have previously participated in electronic learning activities provided by the faculty. Descriptive, correlational, and inferential statistics were resorted to analyse the data. As a result, the study revealed that self-leadership positively predicted electronic learning styles, whereas in fact it negatively predicted critical thinking barriers. Critical thinking barriers negatively predicted electronic learning styles. In closing, for advancing teacher candidates' skills in getting rid of barriers to critical thinking, attention should be given to promote them to find their accurate learning styles through practicing self-leadership. This study can provide evidence for advancing and understanding both policies and theories of self-leadership, electronic learning styles, and critical thinking barriers.